\(a^m.a^n=a^{m+n}\)
\(a^m:a^n=a^{m-n}\)
\(a^m:b^m=\left(a:b\right)^m\)
\(a^m.b^m=\left(a.b\right)^m\)
\(a^{m^n}=a^{m.n}\)
\(a^m\cdot a^n=a^{m+n}\)
\(a^m\div a^n=a^{m-n}\left(a\ne0;\text{ }m>n\right)\)
\(\left(a^m\right)^n=a^{m\cdot n}\)
\(\left(a\cdot b\right)^m=a^m\cdot b^m\)
\(\left(a\div b\right)^n=a^n\div b^n\left(b\ne0\right)\)
\(k^m:k^n=k^{m-n}\)
\(k^m:h^m=\left(k:h\right)^m\)
\(k^m.h^m=\left(k.h\right)^m\)
\(k^m.k^n=k^{m+n}\)
\(k^0=1\)
\(k^1=k\)
\(\left(\frac{k}{h}\right)^m=\frac{k^m}{h^m}\)
\(k^{-n}=\frac{1}{k^n}\)